HEALTH BELIEF MODEL PADA PASIEN YANG BEROBAT KE PENGOBATAN ALTERNATIF - Orin Veronika Damayanti; Michael Seno Rahardanto (Universitas Katolik Widya Mandala Surabaya, 2018)
Alternative medicine is a treatment that uses supernatural powers. This alternative treatment is often used to treat diseases caused by sorcery. Witchcraft or so-called witchcraft is the result of black magicians who aim to satisfy hatred, anger or aggression against someone. There are two medical systems, namely personalistic medical systems and naturalistic systems. This study focuses more on alternative treatments that belong to a personalistic system, a medical system that uses supernatural knowledge with the help of ancestral spirits or jinns to heal its patients. This research uses qualitative research method of case study by using semi-structured interview data retrieval technique. Participants in this study were patients from alternative medicine and those around the participants. The results of this study were the fulfillment of aspects of the health belief model in participants who gave an idea of the reasons of the participants to seek treatment for alternative medicine. The researchers also found some motives that made participants encouraged to go to alternative medicine, namely because of cultural and religious influences believed by participants who later caused a person to experience cognitive dissonance of alternative treatments he has done.